Hukum Perlindungan Konsumen: Jajanan Tidak Layak Konsumsi Masih Beredar - Putra, Fitra; Yama'asura, Irvin; Sofyan, Romiz; Arya, Ferdi (Batulis Civil Law Review, 2023)
The suitability of food for consumers is very important, if you are not careful in choosing food or snacks it can be harmful to your health. There are still many unhealthy snacks circulating in Tulungagung, so people must be more careful in choosing healthy foods to consume. In this case, we make this journal so that consumers can understand and understand the selection of food that is suitable for consumption and it is hoped that consumers will know how dangerous food is that is not suitable if it enters our body. This research was made using qualitative methods. Collecting data using interview and observation techniques. The results of the study are that the majority of food products are considered unfit for consumption because the can packaging is damaged or dented. packaged snacks that have expired but are still displayed by traders/entrepreneurs. Snack products whose trademarks have been engineered by traders. The sales mode that transfers trademarks is carried out by entrepreneurs or traders by buying snack products in large packaging volumes and then repackaging them in smaller volumes at affordable prices.